Cell boundary theorem - Ríos, Eduardo (Henry Stewart Talks, 2012)
Cellular homeostasis, Calcium movements, Movements of Ions and Solutes, A general property that helps determine steady state concentrations in cytosol and organelles, Application to skeletal and cardiac muscle in health and disease, Malignant Hyperthermia, Use of calcium and pH monitoring dyes
Updated at 2020/03/23